2004
DOI: 10.1302/0301-620x.86b8.15012
|View full text |Cite
|
Sign up to set email alerts
|

Fracture of a Y-TZP ceramic femoral head

Abstract: We studied factors contributing to the initiation of fracture and failure of a zirconia ceramic femoral head. The materials retrieved during a revision total hip replacement were submitted to either visual, stereomicroscopic and scanning electron microscopy (SEM) or SEM and energy-dispersive X-ray analysis. X-ray diffraction was performed in order to investigate the extent of tetragonal to monoclinic phase transition. Histological examination was performed on the periprosthetic tissues. The results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
45
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 11 publications
0
45
0
Order By: Relevance
“…SEM analysis of the particles showed the wide difference in the grain size of ceramic precursors particles simulating the clinical condition in case of fracture in which ceramic fragments differs widely In dimension and shape (4,9). Histologic reaction to the periprosthetic tissue membrane reveals a different reaction depending on the grain size.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…SEM analysis of the particles showed the wide difference in the grain size of ceramic precursors particles simulating the clinical condition in case of fracture in which ceramic fragments differs widely In dimension and shape (4,9). Histologic reaction to the periprosthetic tissue membrane reveals a different reaction depending on the grain size.…”
Section: Discussionmentioning
confidence: 98%
“…These studies showed the absence of long-term chronic effects and tumor development (2,3). Moreover in some particular cases ceramic materials may induce an acute reaction to ceramic debris, especially in case offracture (4). The aim ofthis study was to investigate the possible local and systemic acute effects of ceramic precursors in form of powders of different size when released into articular joint.…”
mentioning
confidence: 99%
“…However, Maccauro et al reported on damages to the zirconia femoral heads, which were speculated to be from low-temperature degradation due to an increased monoclinic content 36) . Zirconia restorations have been used prevalently in the intraoral region, but serious issues have not been reported that raise the suspicion of low-temperature degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, the staircase method automatically concentrates testing near the mean and requires fewer tests 26,27) . Hot isostatic pressing was introduced to achieve very high density and enhance the reliability of ceramic components 13,28) . In our preliminary test, HIPed Y-TZP showed very high strength (biaxial flexural strength: approximately 1,800 MPa) compared with Y-TZP fabricated by the normal sintering method in air (biaxial flexural strength: approximately 900 MPa).…”
Section: Discussionmentioning
confidence: 99%